2000
DOI: 10.1074/jbc.275.12.8515
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Magneto-optical Spectroscopic Characterization of Cytoplasmic Membrane and Outer Membrane Multiheme c-Type Cytochromes from Shewanella frigidimarina NCIMB400

Abstract: Two membranous c-type cytochromes from the Fe(III)-respiring bacterium Shewanella frigidimarina NCIMB400, CymA and OmcA, have been purified and characterized by UV-visible, magnetic circular dichroism, and electron paramagnetic resonance spectroscopies. The 20-kDa CymA is a member of the NapC/NirT family of multiheme cytochromes, which are invariably anchored to the cytoplasmic membrane of Gram-negative bacteria, and are postulated to mediate electron flow between quinols and periplasmic redox proteins. CymA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 39 publications
10
109
0
Order By: Relevance
“…Oxidation of lactate to acetate (E°Ј ϭ Ϫ0.42 V) linked to riboflavin reduction (E°Ј ϭ Ϫ0.21 V) provides Ϫ81 kJ/mol free energy, which, at a cost of ATP synthesis of Ϸ60 kJ/mol ATP, allows 1.5 ATP/lactate. This estimate is similar to those based on midpoint potentials of outer membrane cytochromes implicated in metal reduction by Shewanella such as OmcA (Ϫ0.24 to Ϫ0.32 V) (21), and MtrC (approximately Ϫ0.1 V) (22), making 1.5 ATP/ lactate a conservative assumption for ATP yield.…”
Section: Resultssupporting
confidence: 60%
“…Oxidation of lactate to acetate (E°Ј ϭ Ϫ0.42 V) linked to riboflavin reduction (E°Ј ϭ Ϫ0.21 V) provides Ϫ81 kJ/mol free energy, which, at a cost of ATP synthesis of Ϸ60 kJ/mol ATP, allows 1.5 ATP/lactate. This estimate is similar to those based on midpoint potentials of outer membrane cytochromes implicated in metal reduction by Shewanella such as OmcA (Ϫ0.24 to Ϫ0.32 V) (21), and MtrC (approximately Ϫ0.1 V) (22), making 1.5 ATP/ lactate a conservative assumption for ATP yield.…”
Section: Resultssupporting
confidence: 60%
“…This configuration has been shown from modeling to be optimal for electron transfer to insoluble minerals (14) and so this heme is well placed to interact with minerals in the extracellular environment. Consistent with this, electron exchange with solid graphite electrodes probed by PFV is fast, a feature in common with OmcA and MtrC (29,30,32). It is then perhaps surprising that oxidation of reduced MtrF by suspensions of solid ferrihydrite is very slow.…”
Section: Discussionsupporting
confidence: 50%
“…These proteins include CymA, a tetraheme c-type cytochrome anchored to the inner membrane that serves as a MQH 2 dehydrogenase [8,12,20,43,44]; Stc, a 12-kDa tetraheme periplasmic c-type cytochrome [15,45] and the periplasmic decaheme cytochrome MtrA [10] (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Electron transport proteins proposed to be involved in Fe(III) respiration in Shewanella oneidensis MR-1 include an inner-membrane periplasmic tetraheme quinol dehydrogenase (CymA) [8,12], two periplasmic decaheme cytochromes (MtrD and MtrA) [10,13], periplasmic tetraheme cytochrome (Stc) [14,15], the cytochrome domain of Fe(III)-induced flavocytochrome c 3 , [16] two putative outer-membrane b-barrel proteins (MtrE and MtrB) [17][18][19] and three outer-membrane decaheme cytochromes (MtrF, OmcA and MtrC) [11,18,20,21]. Although genetic studies have identified specific proteins that are involved in Fe(III) respiration in Shewanella sp.…”
Section: Introductionmentioning
confidence: 99%